Intercultural learning in the course of Sales Management - Lorente Ayala, José Miguel; Suay Pérez, Francisco; Pérez Lozano, Delia (Journal of Management and Business Education, 2025)
This article analyzes an intercultural collaboration project between students from Tecnológico de Monterrey (Mexico) and Universidad CEU Cardenal Herrera (Spain), aimed at fostering interaction, teamwork, and the development of intercultural competencies. Through synchronous and asynchronous activities, the initiative’s impact on learning and student engagement was evaluated, identifying differences in familiarity with collaborative dynamics and levels of commitment. The results showed high participation and engagement in both groups, but with variations in the quality and consistency of performance. UCHCEU students excelled in asynchronous activities, such as the Icebreaker and Final Reflection, while TEC students faced challenges in maintaining consistent participation. Digital tools and synchronous sessions helped overcome geographical and cultural barriers but revealed the need for better initial orientation and more effective communication strategies. Incentives like digital badges motivated some students, but their impact was limited, suggesting the need for more tiered benefits. Both groups showed improvements across the dimensions of cultural intelligence, with UCHCEU students achieving greater progress in cultural adjustment and self-awareness. The lessons learned highlight the importance of intercultural preparation, continuous monitoring, and communication strategies to strengthen future international collaborations in an interconnected world.